DECISION MAKING FOR ALEXANDERGRASS CONTROL IN MAIZE FOR PESTICIDE-FREE SMALLHOLDER CROPPING SYSTEMS - Almeida, Erexaua Michalski de; Galon, Leandro; Forte, César Tiago; Concenço, Germani; Menegat, Andre Dalponte; Pawelkiewicz, Renan; Brunetto, Leonardo; Müller, Caroline; Perin, Gismael Francisco; Melo, Thais Stradioto; Bernardi, Nathalia Dalla Corte (International Journal of Maize & Sorghum, 2026)
The objective of this work was to evaluate the interference of alexandergrass (Uroclhoa plantaginea) on maize and to determine the economic threshold level (ETL) of this weed under different nitrogen fertilization rates in pesticide-free cropping systems. Treatments consisted of increasing nitrogen doses ranging from 0 to 345 kg ha-1 combined with alexandergrass densities from 0 to 328 plants m-2. Shoot density, leaf area, soil cover, and aboveground dry matter of alexandergrass were evaluated as indicators of weed infestation. Considering typical ranges of maize grain yield, market prices, efficiency, and costs of manual weed control, the most reasonable nitrogen dose for pesticide-free maize production was 200 kg ha-1, as it resulted in the highest ETL values when alexandergrass was present. At this nitrogen level, the ETL should be determined based on the four evaluated infestation parameters; however, on average, weed control should be performed when alexandergrass density reaches between 10 and 15 plants m-2, approximately 21 days after crop emergence. This study provides guidance on the most appropriate timing for controlling alexandergrass by hoeing in pesticide free maize production systems.